Assessing knowledge, beliefs and practices related to the consumption of sheep and goat meat in Senegal - Traoré, Sylvain G.; Fokou, Gilbert; Ndour, Andrée P.N.; Yougbaré, B.; Koné, Philippe; Alonso, Silvia; Roesel, Kristina; Bakou, Serge N.; Dao, Daouda; Grace, Delia; Bonfoh, Bassirou (Elsevier, 2018)
A Rapid Integrated Assessment (RIA) of nutrition and health risks and benefits was carried out in 2013 in sheep and goat agri-food systems in urban and rural Senegal. This included: i) testing small ruminants (n = 384) for brucellosis, ii) focus group discussions of mothers covering knowledge, attitude and practices related to preparation and consumption of animal source food. No antibodies to Brucella melitensis, the presumed priority zoonotic pathogen, were found. Comparing the more traditional, livestock-keeping community with the urban, less livestock-dependent community, we found: urban diets were more diverse, relied more on fish versus livestock products, and used modern products such as yoghurts. Attitudes and beliefs around nutrition and health, strongly shaped the consumption of animal source foods in these contexts.